A set of estimated fiscal rules for a cross section of countries: Stabilization and consolidation through which instruments? - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2013)
This paper provides a set of detailed estimated fiscal reaction functions for a panel of twenty industrialized countries, and it discusses commonalities and differences with regard to systematic fiscal policies across countries. In general, the countries in the panel adjust tax revenues strongly in response to the public debt, and they adjust tax revenues and transfer payments, but, interestingly, not tax rates, strongly in response to output fluctuations. Some countries such as Germany appear to adjust government consumption and investment relatively strongly in response to the public debt, while the United States adjusts capital tax rates relatively strongly. In general, an increased emphasis in the theoretical literature on the effects of procyclical tax revenues and countercyclical transfer payments as automatic stabilizers may be warranted.
Keywords: E62; E63; H20; H62; 330; fiscal policy; fiscal rule; deficits; taxes; government purchases; transfer payments